The Genome of the Endangered Dryas Monkey Provides New Insights into the Evolutionary History of the Vervets. (16th September 2019) - van der Valk, Tom; Gonda, Catalina M; Silegowa, Henri; Almanza, Sandra; Sifuentes-Romero, Itzel; Hart, Terese B; Hart, John A; Detwiler, Kate M; Guschanski, Katerina
Abstract: Genomic data can be a powerful tool for inferring ecology, behavior, and conservation needs of highly elusive species, particularly, when other sources of information are hard to come by. Here, we focus on the Dryas monkey ( Cercopithecus dryas ), an endangered primate endemic to the Congo Basin with cryptic behavior and possibly <250 remaining adult individuals. Using whole-genome sequencing data, we show that the Dryas monkey represents a sister lineage to the vervets ( Chlorocebus sp.) and has diverged from them ∼1.4 Ma with additional bidirectional gene flow ∼750, 000–∼500, 000 years ago that has likely involved the crossing of the Congo River. Together with evidence of gene flow across the Congo River in bonobos and okapis, our results suggest that the fluvial topology of the Congo River might have been more dynamic than previously recognized. Despite the presence of several homozygous loss-of-function mutations in genes associated with sperm mobility and immunity, we find high genetic diversity and low levels of inbreeding and genetic load in the studied Dryas monkey individual. This suggests that the current population carries sufficient genetic variability for long-term survival and might be larger than currently recognized. We thus provide an example of how genomic data can directly improve our understanding of highly elusive species.